2018
DOI: 10.1088/1361-648x/aaade3
|View full text |Cite
|
Sign up to set email alerts
|

Depth dependant element analysis of PbMg1/3Nb2/3O3 using muonic x-rays

Abstract: The relaxor PbMg<sub>1/3</sub>Nb<sub>2/3</sub>O<sub>3</sub> (PMN) has received attention due to its potential applications as a piezoelectric when doped with PbTiO<sub>3</sub> (PT). Previous results have found that there are two phases existing in the system, one linked to the near-surface regions of the sample, the other in the bulk. However, the exact origin of these two phases is unclear. In this paper, depth dependant analysis results from negative muon impla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…clustering of magnesium at the surface for PMN), which leads to changes in the unit cell and strain. [11] Apart from enhancing the understanding of structure, which is central to ferroelectrics research, the skin can also impact macroscopic properties, such as the flexoelectric effect (coupling between polarization and strain gradients). It has been reported that a large flexoelectric effect originates in unpoled BaTiO 3 ceramics due to the presence of a several m thick spontaneously polarized skin, which can be sustained even above the Curie point.…”
Section: Introductionmentioning
confidence: 99%
“…clustering of magnesium at the surface for PMN), which leads to changes in the unit cell and strain. [11] Apart from enhancing the understanding of structure, which is central to ferroelectrics research, the skin can also impact macroscopic properties, such as the flexoelectric effect (coupling between polarization and strain gradients). It has been reported that a large flexoelectric effect originates in unpoled BaTiO 3 ceramics due to the presence of a several m thick spontaneously polarized skin, which can be sustained even above the Curie point.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting point from the XRD results is the observable difference in the diffraction angles of 001/100 peaks between powders and crystals, as shown in the inset of Figure b. This could be attributed to the skin effect, i.e., distinct structures/compositions/properties can exist between the bulk and near-surface layers of the crystal, which is a quite common phenomenon in perovskites. , It is known that the surfaces with no constraint present normal to the surface are able to result in lattice elongation in the surface normal direction. , Upon cooling from above T C , the triaxial stress developed inside the bulk could depress the tetragonal distortion. In contrast, biaxial stress in the surface region gives more freedom for lattice distortion, resulting in large tetragonality ( c / a ratio).…”
Section: Results and Discussionmentioning
confidence: 97%
“…This could be attributed to the skin effect, i.e., distinct structures/compositions/properties can exist between the bulk and near-surface layers of the crystal, which is a quite common phenomenon in perovskites. 23,24 It is known that the surfaces with no constraint present normal to the surface are able to result in lattice elongation in the surface normal direction. 25,26 Upon cooling from above T C , the triaxial stress developed inside the bulk could depress the tetragonal distortion.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] used Muon Induced X-ray Emission (MIXE), while the Ref. [18] used Muonic Atom X-ray Spectroscopy (MAXRS); all of which describe the same technique), a non-destructive technique, which was developed more than 40 years ago [14,[19][20][21], has recently been used extensively with pulsed muon beams for elemental analysis [16,18,[22][23][24][25][26][27][28][29][30][31][32][33][34]. The advantage of this technique is that it is able to probe deep into the material, up to a few millimeters, and does not lead to a severe radiation damage of the sample.…”
Section: Introductionmentioning
confidence: 99%